Enhanced crystallization of solution-processed perovskite using urea as an additive for large-grain MAPbI3 perovskite solar cells. (5th May 2021) - Wen, Xiaoning; Cai, Qingbing; Shen, Guibin; Xu, Xiangning; Dong, Pei; Du, Yaxin; Dong, Hongye; Mu, Cheng
Abstract: Perovskite crystal quality plays an important role in perovskite solar cells, given that multiple grain boundaries and trap states in the perovskite films hamper further enhancement of solar cell efficiency. Using the solution method to prepare perovskite films with large grains and high coverage requires further improvements. Herein, we introduce Lewis base urea as an additive into the precursor of perovskite to control the crystallization dynamics, allowing for large-grain crystal growth. As a result, MAPbI3 films with urea as an additive are well crystallized with large crystal grains of sizes >3 μ m. The large-grain perovskite is found to simultaneously improve the power-conversion efficiency (PCE) and device stability. With an optimal urea additive of 20 mol%, the PCE is significantly increased from 15.47% for the reference MAPbI3 solar cell to 18.53% for the device with MAPbI3 with urea as an additive. Finally, the optimized device demonstrates excellent stability and maintains 80% of the initial PCE after 60 days.